Reinforced Concrete Beam with Openings Strenthened Using CFRP Plate - Ida Bagus Oka Dharmayudha; Noorwirdawati binti Ali (Jurnal Mahasiswa Jurusan Teknik Sipil, 2024)
Adding openings in reinforced concrete beams is one of many options to solve problems around mechanical, electrical, and plumbing (MEP) utilities. However, it came at the cost of reducing the beam load capacity significantly. The opening reduced the cross-sectional area of the beam hence the reduction of stiffness at the opening area. Additionally, the area near the opening is more susceptible to cracking more often and potentially causes a sudden failure. Therefore, external reinforcements are needed to accommodate the strength loss caused by the openings. This study aims to perform a finite element analysis (FEA) of simply supported RC beams with circular openings strengthened using a CFRP plate. The results from finite element analysis are validated using experimental results to ensure the accuracy of the finite element analysis modeling. To perform a finite element analysis finite element software is needed. This study uses ABAQUS to model the specimen and run the finite element analysis inside the software. Inside ABAQUS, a 3D model was built to replicate the experimental specimen as closely as possible with the same material properties, structural analysis, and loading of each specimen. External variables outside the mechanical properties of the model are set as a default value according to ABAQUS. Results show that reinforced concrete beam with an opening has a 15.25% and 32.2% loss of ultimate load capacity from the specimen with 1 and 2 openings respectively. In conclusion, the finite element method can replicate the experimental method to a certain extent. The 3D finite element model can perform crack patterns of reinforced concrete similar to the experimental results. However, the deflection-load curve between the experimental and finite element methods shows a significant difference for all specimens. Keywords: Reinforced Concrete Beam, Beam Openings, CFRP plate, CFRP composite, Finite Element Modelling (FEM), Finite Element Analysis (FEA), ABAQUS